2020
DOI: 10.7717/peerj.8751
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of GLUT4 trafficking in HeLa cells: comparable kinetics and orthologous trafficking mechanisms to 3T3-L1 adipocytes

Abstract: Insulin-stimulated glucose transport is a characteristic property of adipocytes and muscle cells and involves the regulated delivery of glucose transporter (GLUT4)-containing vesicles from intracellular stores to the cell surface. Fusion of these vesicles results in increased numbers of GLUT4 molecules at the cell surface. In an attempt to overcome some of the limitations associated with both primary and cultured adipocytes, we expressed an epitope- and GFP-tagged version of GLUT4 (HA–GLUT4–GFP) in HeLa cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 58 publications
2
18
0
Order By: Relevance
“…Both cell lines grow fast and can be used without the need for differentiation, which was challenging and time-consuming in previous studies [29]. In a recent study, it was demonstrated that HeLa cells expressing a similar GLUT4 fusion protein (HA-GLUT4-GFP) show comparable kinetics and orthologous trafficking mechanisms to 3T3-L1 adipocytes [39], confirming their applicability for our approach. In addition, these cells exhibit good adhesion properties on various surfaces that have been implemented for microscopy, which is especially important for TIRF microscopy.…”
Section: Discussionsupporting
confidence: 55%
“…Both cell lines grow fast and can be used without the need for differentiation, which was challenging and time-consuming in previous studies [29]. In a recent study, it was demonstrated that HeLa cells expressing a similar GLUT4 fusion protein (HA-GLUT4-GFP) show comparable kinetics and orthologous trafficking mechanisms to 3T3-L1 adipocytes [39], confirming their applicability for our approach. In addition, these cells exhibit good adhesion properties on various surfaces that have been implemented for microscopy, which is especially important for TIRF microscopy.…”
Section: Discussionsupporting
confidence: 55%
“…For example, the up-regulation of soluble NSF attachment protein receptors (SNARE) interactions in vesicular transport at exhaustion following ZT0 exercise indicates the increase in a class of membrane-associated proteins, which, besides their involvement in neurotransmitter release (Dunant and Israel, 2000;Kasai et al, 2012), regulate GLUT4-containing vesicle trafficking (Cheatham, 2000). In line, the vesicle-associated membrane protein 3 and 8 (VAMP3, 8), syntaxin 6 and 8 (STX6, 8), synaptobrevin homolog YKT6 (YKT6), and of the synaptosomal-associated protein 23 (SNAP23), which are all key mediators of GLUT4 translocation to the cell surface were elevated at this timepoint (Bryant and Gould, 2011;Morris et al, 2020;Zong et al, 2011).…”
Section: Proteome and Secretome Changes Associated With Daytime Vs Nmentioning
confidence: 82%
“…3T3-L1 murine adipocytes were purchased from ATCC (via LGC Standards, U.S.A. RRID:CVCL_0123) and grown and differentiated as outlined [ 34 , 41 ]. Stable lines of 3T3-L1 fibroblasts expressing HA-GLUT4-GFP had previously been generated in the lab [ 42 ]. Cells were incubated in a 10% CO 2 humid atmosphere incubator at 37°C.…”
Section: Methodsmentioning
confidence: 99%